Managing Early Childhood Care Education for National Consciousness Sustainability in Nigeria - Nimota Jibola Kadir Abdullahi; Abdulmumin Abubakar Lawal; Abdulyaqin Tukur Murtala; Saheed Oyeniran (Indonesian Journal of Economics, Social, and Humanities, 2022)
The main objective of this study was to investigate the effect of management of early childhood care education on national consciousness sustainability. the participants were selected from the sampled public early childhood care education in the northeast zone, of Nigeria. sample of 331 head teachers and 351teachers to make a total of 682 participants were proportionally selected from the sampled schools. Pearson product-moment correlation coefficient and linear regression analysis were used to test the hypotheses. The findings showed that staffing, planning of lessons, and coordination enhanced national consciousness sustainability. Thus, it was recommended that school managers should continue to provide appropriate and adequate staffing of early childhood care education so as to improve the effective development of human capital towards promoting national consciousness sustainability, Also, school managers should encourage caregivers to effectively plan lessons in order to motivate learners and build collaborative processes between teachers and school managers towards the realization of national consciousness sustainability. Furthermore, school managers should continue to coordinate early childhood care education effectively and efficiently so as to ensure mutual understanding and effective teamwork for the realization of national consciousness sustainability.